Quinazoline pharmacophore in therapeutic medicine (Bangladesh Journal of Pharmacology, 2016)
This present study comprehensively expatiates the functionalized utilization of quinazoline scaffolds in drug development and furnishes latest updates in pharmacological appositeness of its derivatives in order to reveal novel pathways for therapeutic targets. It traverses numerous biological potentials of quinazoline in the contemporary time to allow researchers unhindered access to the beneficial role of quinazoline in fighting infectious diseases for future drug discovery. This work provides broad overview of medicinal survey of quinazoline chemistry valuable in the discovery of more efficient clinical trials and to summarize the most promising molecular targets for drug design.